Optimization and Preliminary Physicochemical Characterization of Pectin Extraction from Watermelon Rind (Citrullus lanatus) with Citric Acid - José Pérez; Karina Gómez; Lorena Vega (International Journal of Food Science)
Watermelon rind was used for the pectin extraction with citric acid as the extractant solvent. The effects of pH (2.0-3.0), extraction time (45-75 min), and liquid-solid ratio (10 : 1 to 40 : 1 mL/g) on the pectin yield, degree of esterification, methoxyl content, and anhydrouronic acid content were investigated using Box-Behnken surface response experimental design. The pH was the most significant variable for the pectin yield and properties. The responses optimized separately showed different optimal conditions for each one of the variables studied in this work. Therefore, the desirability function was used to determine the sole theoretical optimum for the highest pectin yield and highest anhydrouronic acid content, which was found to be pH of 2.0, extraction time of 62.31 min, and liquid-solid ratio of 35.07 mL/g. Under this optimal condition, the pectin yield, degree of esterification, methoxyl content, and anhydrouronic acid content were 24.30%, 73.30%, 10.45%, and 81.33%, respectively. At optimal conditions, watermelon rind pectin can be classified as high methoxyl and rapid-set pectin with high quality and high purity. Practical Applications. This study evaluated the pectin extraction from watermelon rind and carried out an optimization of multiple responses as a function of pH, time, and liquid-solid ratio to obtain the best preliminary quality parameters (pectin yield and anhydrouronic acid content). The results revealed that watermelon rind waste can be an inexpensive source to obtain good pectin quality and high purity. According to the chemical characterization and physicochemical properties studied, the extracted pectin from watermelon rind would have a high potential to be used in food industry.